The influence of entrepreneurial mindset and entrepreneurial motivation entrepreneurial readiness - Endang Mulyani; Ahmad Chafid Alwi; Muhammad Roestam Afandi; Supriyanto Supriyanto (Universitas Negeri Yogyakarta, 2023)
This study aims to predict the entrepreneurial readiness of managers based on entrepreneurial motivation and mindset in entrepreneurship. This is necessary because the ratification of universities that previously had the status of PTN-BLU to become PTN-BH demands financial independence, with one of the sources of income being from the business unit sector. This research was carried out at Yogyakarta State University as a newly authorized PTN-BH with business unit managers as the population. The Issac and Michel sampling method determined the sample to be 55 people at random. Using a pragmatic paradigm with quantitative design. The technique used is multiple regression using PLS. The results showed that Entrepreneurial Mindset affects Entrepreneurial Readiness with a t-statistical value of 3,090 with significance levels of 0.002 (proven hypothesis). Entrepreneurial Motivation affects Entrepreneurial Readiness for a t-statistical value of 4,044 and a significance level of 0.000 (this hypothesis is confirmed). Every university that has just been legalized as a PTN-BH must pay attention to the motivation and mindset of its business unit managers, especially business unit managers, generally university staff, who are given additional tasks.